Chatgpt As An Essential Tool: Student Perceptions In Academic Writing At Chlef University - Naimi Amara; Yaqot Elbchir; Aissa Hanifi (The Journal of Studies in Language, Culture and Society, 2025)
The field of artificial intelligence has a lengthy and well-established background, and since its inception, there has been ongoing discourse over its capacity to yield significant scientific breakthroughs. This study examines 22 MA students’ perceptions towards the effectiveness of using ChatGPT in generating high-quality research papers at Chlef University. Participants completed a structured questionnaire with 13 closed-ended questions after using ChatGPT for their research papers. The questions assessed AI’s effectiveness in thesis writing, usage extent, application areas, and overall satisfaction. The analysis revealed that most students integrated AI tools like ChatGPT into their academic work, particularly for dissertations. While students did not find ChatGPT-generated content superior to their own, they believed combining both resulted in the best quality work. High satisfaction levels were noted, despite some limitations. The study also highlighted the need for additional support and training for students unfamiliar with AI tools.